PERTUMBUHAN DAN HASIL KACANG HIJAU DALAM PERSAINGAN DENGAN TEKI DAN RUMPUT BELULANG DI TANAH STERIL DAN NON STERIL - Harmaeni Harmaeni; Wayan Wangiyana (Universitas Pendidikan Mataram, 2018)
This study aimed to determine the effect of competition with nutsedge and Eleucine grasses in autoclave sterilized and non-sterililized soil on growth and yield of mungbean. The experiment was carried out in the glasshouse of the Faculty of Agriculture, University of Mataram, from January to March 2015, arranged in a Completely Randomized Design (CRD), testing 3 treatment factors namely; two soil conditions (autoclave sterilized and non-sterilized), two types of weeds (nutsedge and Eleucine), and weed populations (0, 2 and 4 clumps / polybag), each of which was replicated 3 times, so there were 36 experimental units for each series. The experiment was made in 2 series; first series for measurement of plant dry weight at 6 weeks after seeding, and the second series was for measurement of mungbean seed yield. The results indicated that the three treatment factors affected growth and yield of mungbean. Growth of the mungbean plants was better in the non-sterilized soil compared with in sterilized soil. In terms of weed competition, Eleucine grass was more severe in suppressing growth and yield of mungbean compared with nutsedge grass, whereas of weed population, the treatment without (0) weeds resulted in much better growth of mungbean plants than the treatments of 2 or 4 weeds per polybag